Color Stability of a New Rice Husk Composite in Comparison with Conventional Composites after Exposure to Commonly Consumed Beverages in Malaysia - Kacharaju Kranthi Raja; Padmini Hari; Melissa Queen Kha Chin; Kiran Singbal; Ismail M. Fareez (Hindawi Limited, 2019)
Objective. To evaluate the color stability of a new organic rice husk nanocomposite as compared to four conventional composites after exposure to commonly consumed beverages in Malaysia. Methods. One hundred and twenty-five disk samples were prepared from a new rice husk-based composite and four other conventional methacrylate-based light-cured composites of shade A2. The samples were immersed in four commonly consumed beverages: coco-based drink, kopi, Chinese tea, and teh tarik for four weeks. The color measurements were carried out every week using the reflectance spectrophotometer according to the CIE L∗a∗b∗ color system. Color changes of samples (ΔE) in each week were calculated. Statistical analysis was carried out by performing a mixed ANOVA and Tukey's post hoc test in order to analyse the differences in ΔE. Results. The findings revealed a statistically significant difference of ΔE reading (p<0.05) among all composites immersed in all four beverages after four weeks. Rice husk composites exhibited lesser color stability as compared to Ceram.X One Universal (p<0.001) and G-aenial Universal Flo (p<0.001) but showed higher color stability compared to Solare-X (p<0.001) and Neofil (p<0.001). Coffee and Chinese tea had the most significant impact on color changes (p<0.05) observed in all composites over four weeks of study. Conclusion. Rice husk composite showed acceptable color stability. It can be considered as an alternative to conventional composites due to its eco-friendly properties.